2021
DOI: 10.3126/jalawaayu.v1i1.36446
|View full text |Cite
|
Sign up to set email alerts
|

Elevation Dependency of Precipitation over Southern Slope of Central Himalaya

Abstract: Precipitation plays vital roles in the global water cycle, knowledge of the spatial and temporal variation of the precipitation is essential to understanding extreme environmental phenomena such as floods, landslides, and drought. In this paper, the integrated characteristics of precipitation during 1980–2016 over Nepal along with the seasonal elevation dependency of precipitation were examined for three different regions over the country using Multi-Source Weighted-Ensemble Precipitation (MSWEP) product. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The wet season in Nepal begins from May to November and the dry season from December to February (Sharma et al, 2021). The frequency of typhoid infections in our study is seen throughout the year, but the incidence was high toward the spring season (end of dry season and beginning of wet season) throughout the two-year duration (March 2017 to May 2019).…”
Section: Discussionmentioning
confidence: 45%
“…The wet season in Nepal begins from May to November and the dry season from December to February (Sharma et al, 2021). The frequency of typhoid infections in our study is seen throughout the year, but the incidence was high toward the spring season (end of dry season and beginning of wet season) throughout the two-year duration (March 2017 to May 2019).…”
Section: Discussionmentioning
confidence: 45%
“…Second, atmospheric sounding was more accurate for western than eastern airports because western airports were not situated in mountainous areas. This result suggests the rainfall is related to terrain, elevation, slope, shape, and wind structure and so on [48][49][50].…”
Section: Threshold For Afternoon Convection and Probability Of Precipitationmentioning
confidence: 89%
“…It has been reported that the maximum air temperature has been increasing at high altitudes of Nepal from mid 1970s (Shrestha et al, 1999). Similarly, the precipitation have been reported to be decreasing in far western provinces and higher altitude of Nepal (Sharma et al, 2021;Sharma et al, 2020b). A study of hydro-climatic variability in Karnali river basin of western Nepal illustrated that the maximum temperature trend during the premonsoon season is significantly higher (0.08 o C yr -1 ) followed by winter season during 1981 to 2012 (Khatiwada et al, 2016).…”
Section: Glacier Mapping and Area Changementioning
confidence: 95%